A comparison of three training programs with the same workload on overhead throwing velocity with different weighted balls - van der Tillaar, R.; Marques, M. C. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to determine if different throwing programs based upon velocity (throwing with a regular sized soccer ball), resistance (throwing with heavy medicine ball), or a combination of both with the same workload would enhance 2-handed overhead throwing velocity with different ball weights. Sixty-eight high-school students (16.5 ± 1.8 years, 57.8 ± 12 kg, 164 ± 9 cm), divided into 3 groups, participated in the study. The training programs were matched on total workload, which resulted in the velocity-training group performing 6 series of 14 reps per session with soccer balls, whereas the resistance-training group performed 3 series of 6 throws with a 3-kg medicine ball, and the combination-training group threw 9 times with a 3-kg medicine ball and 3 series of 14 reps with a soccer ball per session. Throwing velocity with a soccer ball, a 1- and 3-kg medicine ball was tested before and after a training period of 6 weeks with 2 sessions per week. A significant (p ? 0.05) increase in throwing velocity was found after the 6-week training period with the soccer ball (6.9%) and the 1-kg medicine ball (2.8%), but not with the 3-kg medicine ball (-2.5%). In contrast, no group interaction was found with the different balls indicating that velocity, resistance, or a combination as a form of training increased the throwing velocity. Different types of training with the same total workload can increase the throwing velocity in a similar way, which shows that workload is of importance in designing training programs and comparing training with each other. Therefore, those that train high-school soccer players could implement any one of these 3 6-week programs to increase 2-handed overhead soccer throw-in velocity. This could allow the throw-in to be harder or potentially thrown farther if the right trajectory is used.